Ambient Environmental Quality Policies in Stochastic Media - Till Requate; Steve Hamilton (Verein für Socialpolitik, 2010)
This paper considers the performance of ambient environmental quality and emissions (effluent) policies in settings where the ability of the receiving environmental media to assimilate pollution is stochastic, for instance a river with variable streamflow. Our main findings are: (i) ambient environmental quality policies welfare dominate emission policies for sufficiently damaging pollutants and for pollutants with sufficiently high abatement costs; (ii) emissions policies tend to induce over-investment in abatement equipment relative to the socially optimal resource allocation, while ambient policies tend to induce under-investment; and (iii) emission policies produce superior outcomes for welfare relative to ambient policies when abatement costs are low. This suggests an optimal lifecycle of environmental regulations may exist in which ambient environmental policies are used in early periods when abatement markets are relatively undeveloped, then emission policies are employed in later periods as cost-effective abatement equipment becomes available.
Keywords: Q20; Q28; Q25; 330; Environmental policy; ambient standards